2020
DOI: 10.1029/2020ms002175
|View full text |Cite
|
Sign up to set email alerts
|

A Kinematic Kinetic Energy Backscatter Parametrization: From Implementation to Global Ocean Simulations

Abstract: Ocean models at eddy-permitting resolution are generally overdissipative, damping the intensity of the mesoscale eddy field. To reduce overdissipation, we propose a simplified, kinematic energy backscatter parametrization built into the viscosity operator in conjunction with a new flow-dependent coefficient of viscosity based on nearest neighbor velocity differences. The new scheme mitigates excessive dissipation of energy and improves global ocean simulations at eddy-permitting resolution. We find that kinema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 45 publications
3
47
0
Order By: Relevance
“…[8]; we refer to [4] for a detailed discussion and relations to other approaches. Simulations with backscatter have been found to provide energy 'at the right place', matching the result more closely to observations and high resolutions comparisons [9].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…[8]; we refer to [4] for a detailed discussion and relations to other approaches. Simulations with backscatter have been found to provide energy 'at the right place', matching the result more closely to observations and high resolutions comparisons [9].…”
Section: Introductionsupporting
confidence: 61%
“…Motivated by the numerical backscatter scheme [4,8,9], we have studied the impact of simplified backscatter via classes of explicit flows in the shallow water and rotating Boussinesq equations on the whole space. Here we have found that backscatter induces unbounded instability of the zero state in the sense of unboundedly and exponentially growing flows, also with vertical structure and also for stable stratification.…”
Section: Discussionmentioning
confidence: 99%
“…A range of theories have been developed, most of which focus primarily on the adiabatic eddy‐driven circulation represented by κ GM (e.g., Cessi, 2008; Eden et al., 2009; Eden & Greatbatch, 2008; Jansen & Held, 2014; Jansen et al., 2015, 2019; Mak et al., 2018; Marshall & Adcroft, 2010; Pearson et al., 2017; Smith & Vallis, 2002; Treguier et al., 1997; Visbeck et al., 1997). Some of these schemes are based on energy conservation and consider the effects of mesoscale eddies in the momentum budget (e.g., Bachman, 2019; Eden & Greatbatch, 2008; Jansen & Held, 2014; Jansen et al., 2019; Juricke et al., 2020). However, the independent choice of the neutral diffusivity κ n has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…This is exacerbated by the fact that backscatter associated with Reynolds stresses (as studied by Grooms et al (2015)) occurs wherever the eddy kinetic energy is large, whereas the backscatter associated with density corrections is confined to a smaller subset of the domain where there are large resolved temperature gradients. Some combination of Reynolds-stress-driven backscatter (e.g., Bachman, 2019; Jansen et al, 2019; Juricke et al, 2020), backscatter associated with density corrections, and other forms of stochastic noise (e.g., Grooms, 2016;Grooms & Kleiber, 2019) may be necessary to achieve a large increase in low-resolution model variability.…”
Section: Summary Of Ocean Responsementioning
confidence: 99%